Naive Bayes Classifier Based Geographic Information System for University Search Information - Junta Zeniarja; Ardytha Luthfiarta; Catur Supriyanto (Journal of Applied Intelligent System, 2017)
Information about the geographical location of universities is necessary for graduates of Senior High School who want to continue their education to a university. Most of the graduate students do not know the location of the universities since the geographical location of Google Maps is less clear and less precise. Therefore, the application of Geographic Information Systems (GIS) based on Information Retrieval (IR) is expected to facilitate the graduate students to know the exact location of the university. In this paper, IR-based GIS application is developed by using web programming. The web is used as a search engine when someone wants to find a college. The application shows the map and information of the college in the area according to the query of the user. Naive Bayes algorithm is used to classify the user query and locate the query on the map. Based on our prototype, the application is promising to be implemented for the student.